Aklisuktuk (Growing Fast) Pingo, Tuktoyaktuk Peninsula, Northwest Territories, Canada - Mackay, J. Ross (ARCTIC, 1981)
Field surveys have been carried out for the 1972 to 1979 period in order to study the growth of Aklisuktuk (Growing Fast) Pingo. The field surveys show that the top of the pingo was slowly subsiding during the seven-year survey period, possibly from a slow downslope glacier-like creep of the ice-rich overburden and ice core. The name "Aklisuktuk" probably dates back at least 200 years. The rapid growth which attracted attention was from accumulation of water in a large sub-pingo water lens.Key words: Aklisuktuk Pingo, sub-pingo water lens, pingo subsidence Mots clés: Pingo Aklisuktuk, poche d'eau au-dessous du pingo, affaissement du pingo